ABO Blood Group Distribution in Patients with Peptic Ulcer Disease - Gonzáles Flores, Pedro (1997)
OBJETIVE: To determinate the ABO blood group distribution in patients with peptic ulcer disease ( PUD ). METHODS: Descriptive and retrospective study. Clinical records of patients with endoscopic diagnosis of peptic ulcer and ABO blood group typification between june 1994 and november 1996 were reviewed. Blood donnors and patients that attended the blood bank between july and august 1996 were taken as controls. RESULTS: 100 patients were studied. In controls 73% were blood group O, whereas in patients with PUD, there were 78% ( p=0.3 ). In duodenal ulcer 85% were «O» ( p=0.04 ) and in those under 40 years, 94 were «O» ( p=0.006 ). CONCLUSIONS: 1) ABO blood group distribution in patients with PUD is similar to control. 2) ABO blood group distribution in duodenal ulcer is statistically different than in control, particullarly in patients under 40 years of age.